Computational Investigation of the Effects of a Shroud to the Aerodynamic Characteristics of Rotors - Le, Thi Tuyet Nhung; Vu, Dinh Quy; Vuong, Cong Dat (Old Journal, 2019)
Multicopters or multirotors have become standouts because they can hover and vertically take off and land. When they are in action, multirotors may need shrouds to protect their blades from impact and protect human from being wounded. However, the effects of shrouds to the aerodynamic characteristics of rotors must be considered. This paper will use computational fluid dynamics (CFD) to investigate the effects of a shroud to the thrust and power of a 9.5-inch rotor and 15-inch rotor. The results show that at the same rpm, a shrouded rotor can produce 20% more thrust than a free rotor. The power also increases but only by 6%. These results of 9.5-inch rotors agree with Baeder’s results (2011), therefore, we apply to the case of 15-inch APC 15×4 blades in real life.